ANALISIS PERBANDINGAN EFISIENSI BANK UMUM SYARIAH DI INDONESIA DENGAN METODE DATA DEVELOPMENT ANALYSIS (DEA) - alimatul Akhyu Al-Ulya (Universitas Gajayana Malang, 2019)
Abstract: The aim of this study is to compare the efficiency level of Islamic Commercial Banks in Indonesia listed on a national bank and financial service authority in 2015-2017. The method used in this study is the method of Data Envelopment Analysis that assumed Constant Return to Scale (CRS). The result of the calculation of technical efficiency by using DEA from the performance of Islamic Commercial Banks in Indonesia in 2015-2017 that have not been effective yet. As for bank who received a score of efficiency highest during the period of research they were Bank Maybank Sharia Indonesia with score 100%. While the bank who received scores of efficiency lowest is Bank BRI Sharia with score 75.06%. Keywords: Islamic Commercial Banks, Efficiency, Data Envelopment Analysis (DEA).